Pengaruh Bukaan Pada Ruangan Rumah Type 36 Terhadap Kenyamanan Termal Menurut Persepsi Pengguna - Yeni Bayak Miko; Sri Nengsih; Zia Faizurrahmany El Faridy (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
A house as a shelter for the occupants requires ventilation, both natural and artificial, to achieve thermal comfort. Openings allow air to circulate in and out of the building, thus affecting the humidity and temperature of the building. The research was located in the Type 36 Mutiara Baet Residence housing complex, in Baet Village, Baitussalam District, Aceh Besar Regency. The case study is a house facing west, east, north, and south which has openings without direct sunlight. Using a mixed method research method, which combines qualitative and quantitative models.